Pierre Boulez im Austausch mit Heinrich Strobel, Baden-Baden, 1950/1951: Ein Briefwechsel mit neuen Perspektiven auf Polyphonie X und Boulez’ Ablehnung der Idolisierung Anton Weberns - Zenck, Martin (Die Musikforschung, 2024)
The article starts from the premises of Pierre Boulez’s works of the 1940s, in which the poems of René Char (Le soleil des eaux) and Stéphane Mallarmé (Un coup de dés) took centre stage. On closer inspection, they led to the creation of Polyphonie X. The focus of the article is on the one hand an unpublished letter in which Boulez criticises the ideologisation of Webern’s music by René Leibowitz and others, on the other hand Boulez’s close relationship with Heinrich Strobel, the head of the music department of Südwestfunk in Baden-Baden, who also commissioned Boulez to compose Polyphonie X. This work was performed in the composer’s absence on 6 October 1951, a world premiere that was plagued by tumult, and the regional press did not shy away from making anti-Semitic accusations about the work. Nevertheless, his friendship with Heinrich Strobel remained intact and even led to Boulez feeling so at home in Baden-Baden that he moved to Kapuzinerstraße in 1958. Another reason for making his home in Germany was his critique of the French cultural system headed by secretary of state André Malraux, and the treatment of the Algerians by the French government. Baden-Baden remained Boulez’s first and only permanent residence until his death on 6 January 2016: the personal, intellectual and artistic centre of this cosmopolitan.